2019
DOI: 10.1002/lpor.201800274
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Near‐field Enhancement with Hybrid Metal‐Dielectric Oligomers

Abstract: Tailoring of the near‐field properties of the nanostructures is a significant task for the control of radiation of nanoscale light sources as well as for sensing applications. Generally, this task is solved in plasmonic oligomers on the fabrication step by the choice of geometry or by controlling the excitation light during the experiments. Here, the pronounced modification of the near‐field pattern in hybrid gold‐silicon oligomers by femtosecond laser reshaping by visualizing it with aperture‐type near‐field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Zuev et al [ 12 ] demonstrated the fabrication of hybrid nanostructures with a magnetic optical response via femtosecond laser melting of asymmetrical metal–dielectric (Au/Si) nanoparticles created by lithographical methods. Furthermore, such asymmetrical hybrid nanostructures can be used to locally color the surface in a tunable way [ 13 ], as well as fano resonance [ 14 ] and near-field distribution [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zuev et al [ 12 ] demonstrated the fabrication of hybrid nanostructures with a magnetic optical response via femtosecond laser melting of asymmetrical metal–dielectric (Au/Si) nanoparticles created by lithographical methods. Furthermore, such asymmetrical hybrid nanostructures can be used to locally color the surface in a tunable way [ 13 ], as well as fano resonance [ 14 ] and near-field distribution [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the way of integration of plasmonics with the highrefractive dielectics, hybrid Si/Au(Ag) nanostructures with separated metallic and semiconductor parts were recently applied for surface coloring 10 , near-field and far-field tuning 11 , optical harmonics generation 12 , and fluorescence enhancement 13 . However, standard top-down approaches, combining these elements within a single nano-objects, are complicated and often restricted by the material properties.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was observed with a near-field optical microscope. [247] Metallo-dielectric core-shell nanostructures play an important role in the development of more efficient sensing devices. In ref.…”
Section: Sensing and Sersmentioning
confidence: 99%
“…Apart from nonlinear frequency generation, nonlinear effects can also be used for the purpose of all‐optical dynamic tuning of the optical response of hybrid metal‐dielectric nanostructures. For example, metal‐dielectric metasurfaces allowing for dynamic beam steering, [ 314 ] tunable topological insulators, [ 315 ] and metamaterials reconfigurable by a fs laser pulse [ 247 ] were reported.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation